2018
DOI: 10.1080/17460441.2018.1457645
|View full text |Cite
|
Sign up to set email alerts
|

Have there been improvements in Alzheimer’s disease drug discovery over the past 5 years?

Abstract: Alzheimer's disease (AD) is the most important neurodegenerative disorder with a global cost worldwide of over $700 billion. Pharmacological treatment accounts for 10-20% of direct costs; no new drugs have been approved during the past 15 years; and the available medications are not cost-effective. Areas covered: A massive scrutiny of AD-related PubMed publications (ps)(2013-2017) identified 42,053ps of which 8,380 (19.60%) were associated with AD treatments. The most prevalent pharmacological categories inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 74 publications
0
38
0
2
Order By: Relevance
“…The purpose of a vaccine is not to resuscitate dying neurons but to prevent their premature neurodegeneration. Therefore, the clinical trial design has to be adapted to this new therapeutic modality, not reproducing obsolete procedures used for the clinical testing of symptomatic drugs (with no breakthroughs during the past 20 years) [1]. In this regard, regulatory authorities (FDA, European Medicines Agency, Koseisho, and other national regulators), together with the pharmaceutical industry and the scientific community, have to design novel protocols for preventive intervention in AD.…”
Section: Expert Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of a vaccine is not to resuscitate dying neurons but to prevent their premature neurodegeneration. Therefore, the clinical trial design has to be adapted to this new therapeutic modality, not reproducing obsolete procedures used for the clinical testing of symptomatic drugs (with no breakthroughs during the past 20 years) [1]. In this regard, regulatory authorities (FDA, European Medicines Agency, Koseisho, and other national regulators), together with the pharmaceutical industry and the scientific community, have to design novel protocols for preventive intervention in AD.…”
Section: Expert Opinionmentioning
confidence: 99%
“…After almost 20 years of therapeutic stagnation in Alzheimer's disease (AD), despite important investment and scientific effort [1], some reflections are opportune concerning strategies in drug development, especially immunotherapy and AD vaccination. It was a great achievement to demonstrate that AD is the result of a neurodegenerative process which commences decades before the onset of the disease, caused by multifactorial events (genomic defects, epigenetic dysregulation, cerebrovascular damage, and diverse environmental factors), in order to implement potential prophylactic/preventive strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Serious cognitive dysfunctions in AD patients result from disruptions of neural circuitry due to failure in coordinated development of neural processes provoked by pathological events at the intra-and extracellular brain levels. [1][2][3] One of the key factors playing a role in this pathology is a defect in amyloid precursor protein excretion. [1][2][3] Excessive accumulation of amyloid beta in the brain is accompanied by the formation of plaques around the nerve cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] One of the key factors playing a role in this pathology is a defect in amyloid precursor protein excretion. [1][2][3] Excessive accumulation of amyloid beta in the brain is accompanied by the formation of plaques around the nerve cells. Noticeably, pathological processes develop not only in the intracellular matrix but also inside the neurons: it was shown that the content of microtubule-associated tau protein extremely increases in AD patients causing interruption of normal neural networks activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation